2021
DOI: 10.3390/v13050945
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neutralizing Antibodies to Canine Distemper Virus and Response to Vaccination in Client-Owned Adult Healthy Dogs

Abstract: Re-vaccinations against canine distemper virus (CDV) are commonly performed in 3-year intervals. The study’s aims were to determine anti-CDV antibodies in healthy adult dogs within 28 days of vaccination against CDV, and to evaluate factors associated with the presence of pre-vaccination antibodies and with the antibody response to vaccination. Ninety-seven dogs, not vaccinated within 1 year before enrollment, were vaccinated with a modified live CDV vaccine. A measurement of the antibodies was performed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…A study by Bergmann et al . [ 44 ] reported that the survival of canine distemper virus in a stray dog population was constant at different ages, whereas Temilade et al . [ 24 ] demonstrated that the disease onset was more likely within the period from birth until 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bergmann et al . [ 44 ] reported that the survival of canine distemper virus in a stray dog population was constant at different ages, whereas Temilade et al . [ 24 ] demonstrated that the disease onset was more likely within the period from birth until 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A potential candidate for such control could be canine distemper virus (CDV), a cousin of measles virus. With CDV, although it is often not necessary, it is common to revaccinate, but the vaccination boost may be inhibited by residual immunity [ 96 ]. Such immunity would not be expected to interfere with a nucleic acid-based vaccine, so using a mRNA platform is a logical approach worthy of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…This interference is more an issue with some types of vaccine than others with live attenuated vaccines being the most susceptible. In veterinary medicine, for example there is often a need to revaccinate against CDV, a cousin virus of measles, but pre-existing immunity can interfere with the response [ 96 ]. This pre-existing immune inhibition should not be an issue with genetic vaccines particularly the mRNA vaccines since they will not be inhibited by pre-existing antibodies and only express proteins after the genetic material has entered cells and been expressed for processing to stimulate T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, antibody titration could allow to identify the so-called non-responder dogs, meaning those dogs that are unable to mount a protective immunity after vaccination or pathogen direct contact (generally they fail to seroconvert to one of the core vaccine antigens, such as CPV-2 or CDV). In literature, it is reported that 1 out of 5000 dogs may be a non-responder to CDV [ 2 , 15 ]. For all these reasons, in recent years, serological testing has been progressively introduced in veterinary practices to know the real protection status of dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for detection of CDV antibodies in dogs is the virus neutralization (VN) test that is usually performed in specialized diagnostic laboratories [ 15 ]. However, the WSAVA guidelines supports the use of rapid serological in-clinic tests for the determination of antibody titers for core vaccines in dogs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%